Adaptation to blindness in Nigeria : case study of the Pacelli School, Lagos - Anumonye, Amechi (Lagos, Nigeria : Lagos University Press, 1981)
The reason for this case study on blindness has been the lack of basic teaching data in almost all areas of psychological medicine, which has specific relevance to Nigeria.
Includes notes.
Includes bibliographical references: p. 141-143.
II 18/01/2019
Loans
Keywords: Blind children